2012
DOI: 10.1007/s00428-012-1198-y
|View full text |Cite
|
Sign up to set email alerts
|

Histological and clinical characteristics of malignant giant cell tumor of bone

Abstract: Malignant giant cell tumors of bone (MGCTB) are rare, and the diagnosis can be difficult due to the occurrence of a variety of malignant tumors containing giant cells. To better understand its clinicopathological features, we have reviewed our experience with 17 cases of MGCTB. Five cases were primary malignant giant cell tumor of bone (PMGCTB), and 12 cases were giant cell tumors of bone initially diagnosed as benign but malignant in a recurrent lesion (secondary MGCTB, SMGCTB). The patients included six wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
85
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(90 citation statements)
references
References 23 publications
3
85
0
2
Order By: Relevance
“…Most of the malignant GCTB evolve years after surgery and are associated with previous radiotherapy or occur de novo. On the other hand, cases of sarcomatous transformation in sites of GCTB following surgery alone have also been reported (so-called primary malignant GCTB) [1,12,13,17,29,30]. Usually the malignant transformation of the GCTB has the morphology of osteosarcoma, fibrosarcoma, or so-called malignant fibrous histiocytoma (secondary malignancy in GCTB) [5,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the malignant GCTB evolve years after surgery and are associated with previous radiotherapy or occur de novo. On the other hand, cases of sarcomatous transformation in sites of GCTB following surgery alone have also been reported (so-called primary malignant GCTB) [1,12,13,17,29,30]. Usually the malignant transformation of the GCTB has the morphology of osteosarcoma, fibrosarcoma, or so-called malignant fibrous histiocytoma (secondary malignancy in GCTB) [5,29].…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, the malignant transformation is diagnosed within five years following primary resection. Various oncogenes and tumor suppressor genes, including p53 and H-ras, are thought to affect this transformation [12,13,17,30]. Okubo et al reported that p53 and high GPX-1 expression is of great help in diagnosing malignant transformation in GCTB [12].…”
Section: Discussionmentioning
confidence: 99%
“…Although GCT is predominantly regarded as benign lesion, it has malignant potential and could completely transform into malignant one [11]. Only 1.4-9.4 % of GCTs appear in the spine and occur most commonly between the ages of 20-40 years, with a male-to-female ratio of 1:2.5 [1,[3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Primary MGCT (PMGCT), which is often diagnosed at the time of first treatment, has a juxtaposition of conventional giant cell areas and pleomorphic spindle cell areas that are clearly malignant [10]. Secondary malignant giant cell tumor (SMGCT) is a high-grade sarcoma occurring as a recurrent lesion at the site of a benign GCT either after surgery, radiotherapy, or both [9,11]. SMGCT is more common than PMGCT and mainly originates after irradiation treatment for the primary lesion [8,[12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There is marked subjectivity in the histopathological grading systems and many reports on the correlation of histological features and prognosis have concluded that it is impossible to judge whether or not a GCT of bone is likely to recur from its histological characteristics. 4,15 At present, no grading system has proved to have prognostic relevance. Recent understanding of the cellular components of GCT and its molecular and cytokine-mediated derivation has shed new light on the nature of GCT.…”
Section: Discussionmentioning
confidence: 99%